Performance and potential of gramasabhas in crop production in Athiyanoor block of Thiruvananthapuram district - Beena S (Department of Agricultural Extension, College of Agriculture, 2002)
The study entitled 'Performance and potential of gramasabhas in crop production. in Athiyanoor block of Thiruvananthapuram district was undertaken to study the effectiveness, attitude and perception and to identify the constraints as perceived by the farmers, officials and people's representatives regarding the functioning of gramasabhas. The study was conducted in Venganoor, Vizhinjam, Athiyanoor and Kottukal panchayats of Athiyanoor block. A sample of 200 respondents were selected using multistage random sampling technique. Data were collected through well structured and pre-tested interview schedule. Sixty per cent of the farmers, fifty five per cent of the officials and sixty per cent of the people's representatives perceive the gramasabhas as effective in planning and implanting agricultural development programmes. Regarding the attitude towards gramasabhas, 58.43 per cent of the farmers and 87.50 per cent of the people's representatives possessed a very favourable attitude. Among the officials, 65 per cent were favourable towards gramasabhas. Eighty per cent of the people's representatives had very good perception about the functioning of gramasabhas. The study revealed that 57.50 per cent of the officials and 61.67 per cent of the farmers belonged to high group with respect to perception. Majority of the farmers had education upto high school level with farming as the main occupation. Most of the farmers expressed a high level